Gentrification of Trusmi Batik Cirebon - Khairune Nisa, An Nuur (Jurnal Toursci, 2023)
This study aims to photograph the immigration of middle-class residents to urban areas that are in poor condition or have recently been refurbished or modernized. This study uses a qualitative approach to see the phenomenon of Trusmi Village as the heart of batik production in Cirebon. They involve thousands of batik artisans working daily from residents of Trusmi village and its surroundings, such as Gamel, Kaliwulu, Wotgali, and KaliTengah. Shops and showrooms showcase artisans' finest products along 1.5 kilometers of Trusmi Street. Batik showrooms in the form of shops line the village streets in various sizes and shapes. UNESCO recognizes Indonesian Batik as one of the intangible world cultural heritage. Ironically, the wages of batik artisans are meager. Due to labor shortages, about 60 percent of the 360 batik SME industries in Cirebon Regency have gone out of business in the last five years. Old artisan mothers dominate the batik-making centers in Trusmi Village over the age of 4